Simplified endoscopic pressure study integrated system for the diagnosis of gastroesophageal reflux disease. Issue 4 (22nd March 2021) - Nishikawa, Yohei; Inoue, Haruhiro; Shimamura, Yuto; Abad, Mary Raina Angeli; Fujiyoshi, Yusuke; Owada, Kaori; Toshimori, Akiko; Tanabe, Mayo; Ikeda, Haruo; Onimaru, Manabu
Abstract : Endoscopic pressure study integrated system (EPSIS) is a novel tool for the diagnosis of gastroesophageal reflux disease. It enables the evaluation of the function of the lower esophageal sphincter by monitoring intragastric pressure (IGP) while insufflating the stomach during esophagogastroduodenoscopy. EPSIS can predict abnormal acid reflux with high accuracy based on previous studies. IGP was measured by inserting through the working channel of the scope an intragastric catheter connected to a pressure measuring device. Herein, we assess the feasibility of an updated EPSIS system, which can be performed just by connecting a flush tube to the working channel. This method does not require inserting foreign objects in the stomach and spares catheter insertion in order to simplify the procedure and reduce costs. A single‐center pilot study was conducted to evaluate the association between catheter‐based EPSIS and the updated EPSIS. The results of EPSIS in 20 patients who underwent both methods were assessed. In all cases, the waveform pattern of IGP measured by catheter‐based EPSIS and updated EPSIS was consistent with 15 uphill pattern and five flat pattern. Intraobserver agreement of waveform pattern was perfect between two examiners with kappa value = 1. Intraclass correlation coefficient (ICC) for intraobserver reliability for maximum IGP was excellent with 0.91 (95% confidence interval [CI] of 0.77 < ICC < 0.96) and for pressure gradient was also good with 0.89 (95% CI of 0.71 < ICC < 0.95). In conclusion, our study suggests that the updated EPSIS can be performed without the use of a catheter.